Determination of the Unilaterally Damaged Region May Depend on the Asymmetry of Carotid Blood Flow Velocity in Hemiparkinsonian Monkey: A Pilot Study. (9th November 2022) - Seo, Jincheol; Lim, Kyung Seob; Jeon, Chang-Yeop; Baek, SeungHo; Yeo, Hyeon-Gu; Choi, Won Seok; Park, Sung-Hyun; Jeong, Kang Jin; Won, Jinyoung; Kim, Keonwoo; Park, Junghyung; Cho, Jiyeon; et al.
Abstract : The hemiparkinsonian nonhuman primate model induced by unilateral injection of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) into the carotid artery is used to study Parkinson's disease. However, there have been no studies that the contralateral distribution of MPTP via the cerebral collateral circulation is provided by both the circle of Willis (CoW) and connections of the carotid artery. To investigate whether MPTP-induced unilaterally damaged regions were determined by asymmetrical cerebral blood flow, the differential asymmetric damage of striatal subregions, and examined structural asymmetries in a circle of Willis, and blood flow velocity of the common carotid artery were observed in three monkeys that were infused with MPTP through the left internal carotid artery. Lower flow velocity in the ipsilateral common carotid artery and a higher ratio of ipsilateral middle cerebral artery diameter to anterior cerebral artery diameter resulted in unilateral damage. Additionally, the unilateral damaged monkey observed the apomorphine-induced contralateral rotation behavior and the temporary increase of plasma RANTES. Contrastively, higher flow velocity in the ipsilateral common carotid artery was observed in the bilateral damaged monkey. It is suggested that asymmetry of blood flow velocity and structural asymmetry of the circle of Willis should be taken into consideration when establishing more efficient hemiparkinsonian nonhuman primate models.